Sequence polymorphism of mitochondrial DNA HVS II region of Malay population of peninsular Malaysia - Wahab, Mohd Faizul Abd (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2008)
Sequence variation in hypervariable II region (HVS-II) in the control region of mitochondrial DNA (mtDNA) was studied in 45 unrelated Malay individuals by PCR amplification and direct sequencing. A 267 bp fragment of HVS-II region was amplified using a set of primer HVC1 and HVDI. Agarose gel electrophoresis was carried to examine the polymerase chain reaction product. The product was purified prior to sequencing using QIAquick PCR Purification kit (QIAGEN). A total of 45 samples were sent for sequencing, but only 40 samples were successfully sequenced. Within the 40 sequences, 39 different haplotypes were observed, which 2 individuals shared the same haplotypes. From the result obtained, 42.5% of the samples were classified under haplogroup M, 12.5% were classified under haplogroup B, 10% were classified under haplogroup F and another 5% were classified under other haplogroup, D. A total27.5% of the samples were not yet classified.